Réponses

2014-05-05T19:11:28+02:00
y=-2/3x+5/3
y=5/4x+1


-5/4x = 1-y
x = -4/5 +4/5y

donc
y = -2/3(-4/5+4/5y ) +5/3
y = 8/15 -8/15y +25/15
y = -8/15y +33/15
y+8/15y =33/15
15/15y+8/15y = 33/15
23/15y = 33/15
y = 33/15 *15/23
y = 33/23

x = -4/5 +4/5y
x =-4/5 +4/5 (33/23)
x = -4/5 +132/115
x = -92/115 +132/115
x =40/115
x = 8/23

2014-05-05T19:20:00+02:00
y=-2/3x+5/3
y=5/4x+1
 

-5/4x = 1-y
x = -4/5 +4/5y

donc 
y = -2/3(-4/5+4/5y ) +5/3
y = 8/15 -8/15y +25/15
y = -8/15y +33/15
y+8/15y =33/15
15/15y+8/15y = 33/15
23/15y = 33/15
y = 33/15 *15/23
y = 33/23

x = -4/5 +4/5y
x =-4/5 +4/5 (33/23)
x = -4/5 +132/115
x = -92/115 +132/115
x =40/115
x = 8/23